Pemenuhan Hak Tahanan dan Narapidana Disabilitas Fisik di Lembaga Pemasyarakatan Kelas Iia Lombok Barat dan Rumah Tahanan Negara Kelas Iib Praya - Mokoagow, Furqi Sultan; Iskandar, Irvan Sebastian (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to examine the fulfillment of rights for physically disabled inmates at Class IIA Correctional Institution in West Lombok and Class IIB State Detention Center in Praya. The background of this research lies in the suboptimal realization of basic rights for inmates with disabilities, despite the legal guarantees provided by Law No. 8 of 2016 and Law No. 22 of 2022. The central question raised is how the implementation of these rights is carried out during the period of incarceration. The study employs a descriptive qualitative method using a case study approach. Data collection techniques include observation, interviews, and documentation. Analysis was conducted inductively by referring to Human Rights Theory and the Ethics of Care. The results show that although there are some facilities such as disability-accessible pathways and special housing blocks, significant deficiencies remain, especially regarding inappropriate toilet facilities, limited personnel, and the readiness of technical implementing units constrained by budget limitations. The study concludes that the fulfillment of rights for disabled inmates is still not fully optimal, and improvements in infrastructure, regulatory frameworks, and human resource capacity are required to align with the principles of non-discrimination and justice.